Recombinant Tissue Plasminogen Activator Enhances Microglial Cell Recruitment after Stroke in Mice. Issue 5 (May 2014) - Lenglet, Sébastien; Montecucco, Fabrizio; Denes, Adam; Coutts, Graham; Pinteaux, Emmanuel; Mach, François; Schaller, Karl; Gasche, Yvan; Copin, Jean-Christophe
The effect of recombinant human tissue plasminogen activator (rtPA) on neuroinflammation after stroke remains largely unknown. Here, we tested the effect of rtPA on expression of cellular adhesion molecules, chemokines, and cytokines, and compared those with levels of inflammatory cell recruitment, brain injury, and mortality over 3 days after transient middle cerebral artery occlusion (MCAO) in mice. Mortality was dramatically increased after rtPA treatment compared with saline treatment during the first day of reperfusion. Among the animals that survived, rtPA significantly increased CCL3 expression, microglia recruitment, and cerebral infarction 6 hours after MCAO. In contrast, the extent of neutrophils and macrophages infiltration in the brain was similar in both saline- and rtPA-treated animals. Recombinant human tissue plasminogen activator induced II 1b and Tnf expression, 6 and 72 hours after MCAO, respectively, and dramatically reduced interleukin 6 (IL-6) level 24 hours after reperfusion. A dose response study confirmed the effect of rtPA on CCL3 and II1b expressions. The effect was similar at the doses of 1 and 10 mg/kg. In conclusion, we report for the first time that rtPA amplified microglia recruitment early after stroke in association with a rapid CCL3 production. This early response may take part in the higher susceptibility of rtPA-treated animals to reperfusion injury.